Emergence of Non-Serotype b Encapsulated Haemophilus influenzae as a Cause of Pediatric Meningitis in Northwestern Ontario - Pouya Sadeghi-Aval; Raymond SW Tsang; Frances B Jamieson; Marina Ulanova (Canadian Journal of Infectious Diseases and Medical Microbiology)
Before the introduction of the conjugate vaccine, Haemophilus influenzae serotype b (Hib) was the leading cause of bacterial meningitis in children. Although successful in reducing Hib cases, the vaccine confers no protection against other serotypes of H influenzae, such as a (Hia), or f (Hif). The emergence of invasive disease caused by non-Hib in northwestern Ontario (38 cases between 2002 and 2008) with predominance of Hia was previously reported by the authors. At that time, no cases of pediatric meningitis caused by H influenzae were recorded in the region. Continued surveillance identified 12 new cases of invasive non-Hib between January 2009 and July 2011. Among these cases, three young children developed meningitis with severe complications caused by Hia or Hif. The present article describes these cases along with the characteristics of recent H influenzae isolates from the region, (ie, their genetic background and antibiotic sensitivity). The findings point to the clonal nature of circulating Hia strains as well as to an increase in frequency and severity of pediatric invasive H influenzae infections in northwestern Ontario.